PENERAPAN MODEL PROBLEM BASED INSTRUCTION (PBI) BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR MURID MATERI SIKLUS AIR KELAS V SEKOLAH DASAR - Patue, Cindy Desiani Mustafa; Meylan Saleh; Rifda Mardian Arif; Gamar Abdullah; Kudus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the learning outcomes of fifth-grade students on the water cycle through the application of the Problem Based Instruction (PBI) model assisted by Audio Visual media at SDN 5 Tilongkabila. The type of research used is Classroom Action Research (CAR). Data collection techniques used are observation, tests, and documentation. The results of the study show that student learning outcomes have improved in each cycle. During the initial observation, 10 students, or 40%, achieved learning mastery, while 15 students, or 60%, had not yet achieved it. In Cycle I, this figure increased to 18 students, or 72%, achieving learning mastery, and 7 students, or 28%, having not yet achieved it. Furthermore, in Cycle II, this figure increased again to 22 students, or 88%, achieving learning mastery, and 3 students, or 12%, having not yet achieved it. Based on these research results, it can be concluded that the application of the Problem-Based Instruction (PBI) model with the aid of audio-visual media to the water cycle can improve the learning outcomes of fifth-grade students at SDN 5 Tilongkabila.